Paskutiniai Emmanuelio Levino tėvų namai Kaune ir tėvo verslo reikalai (pagal keletą naujai surastų dokumentų) = The Last House of Emmanuel Levinas’ Parents in Kaunas and His Father’s Business (According to Some Newly Discovered Documents) - Pažėraitė, Aušra Kristina (Religija ir kultūra, 2014)
The article presents reasoned material concerning a house in Kaunas, No. 27D A. Mickevičiaus Street, where Emmanuel Levinas’ parents lived at least from 1936 until their violent death during the Second World War. Arguments are based on archival documents, related to the household (on No. 19, A. Mickevičiaus Street) that belonged to Feige and Nison Misleris in the interwar period, and on the local survey of the current location. In the second part of the article, presented are documents from the tax office of the Municipality of Kaunas district (1936-1939), related to the stationery supplies of Emmanuel Levinas’ father, Jechiel Levinas. These documents reveal that the stationery shop was small (located only in one small room, with no warehouse and only one assistant, "garcon"). Its turnover of goods was low, even though the tax institutions used to annually (1936-1939) conclude that the turnover is rising, thereby increasing the tax percentage rate, and arguing that the office is old and has a steady flow of clientele. For two years Jechiel Levinas managed to protest this conclusion with the issue to recognize the turnover of 1934; nevertheless, he failed in 1939. In his protests, Jechiel Levinas wrote to the competent tax authorities, complaining that business is declining, not rising, and that the increasing taxes may ruin it completely.